Embodied religion’s radicalisation of immanence and the consequent question of transcendence - Anné Verhoef (Acta Academica, 2013)
Transcendence has lost its metaphysical moorings and the tendency in postmodernity is the sublimation of transcendence within a conceptual framework of immanence. In other words, transcendence, in a postmetaphysical world, is fully and absolutely actualised or embodied. The consequent question arises: Is there still a need for the concept of transcendence and how should this transcendence be understood in the religious context, in particular? This question is explored by first analysing transcendence within the science-religion discourse. Secondly, Sally McFague’s theology is discussed as an example of a theology of radical immanence, and lastly Gilles Deleuze’s concept of radical immanence is explored. I argue that an understanding of embodied religion in a radical immanent way raises some intrusive questions concerning both the concept of transcendence and religion. A reinterpretation of transcendence might, however, make it possible to understand embodied religion not only in radical immanent terms.